The challenges in implementing cash waqf in Malaysia / Nurwajihah Ajlaa Ali and Ruzian Markom - Ali, Nurwajihah Ajlaa; Markom, Ruzian (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Cash waqf is one of the contemporary instrument for Islamic Social Finance (ISF). It has the potential to address social issues in promoting and enhancing the economic, educational, health, religious, and social development of the Muslim communities. Recently, the use of cash waqf is continually evolving and improving in many Muslim countries due to its flexibility and accuracy. However, the implementation of cash waqf in Malaysia faces a few issues and challenges such as inadequacy of comprehensive legislation and regulatory framework, lack of management skills among related entities, lack of a regulatory mechanism to ensure the collections of cash waqf are transparent and complete as well as lack of transparency in channelling the funds to the specified beneficiaries. The study analyzed the meaning and concept of cash waqf by identifying its characteristics and development in Malaysia. Besides, the study explores challenges in implementing cash waqf within the system. This study utilized the doctrinal research method with content analysis. The systematic review on the topic will be undertaken with emphasis on understanding issues, challenges, laws, policy and methods for waqf. The gap of current practices and issues facing by State Islamic Religious Council (SIRCs) and other related entities will also be identified. The content analysis aids learning from past research and documented evidence on different issues and challenges within the cash waqf institution. Data collection from the library consisting of primary and secondary sources such as statutes, books, and articles. Findings of the study showed that there is a need for proper waqf legislation, sound management policies, sustainable governance framework well as technological innovation to enhance cash waqf collection and development in Malaysia.